ANALISIS PEMAHAMAN MASYARAKAT TERHADAP HAUL DAN NISAB ZAKAT HARTA PERSPEKTIF HUKUM ISLAM - Umar B; Hartini Tahir; Musyfikah Ilyas (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam, 2023)
Abstract The main problems of this study are 1) How is the community's understanding of the haul and nizab of zakat assets in Lagading Village, Pitu Riase District, Sidenreng Rappang Regency, 2) How are the efforts of the Lagading Village government, Pitu Riase District, Sidenreng Rappang Regency in providing understanding to the community regarding haul and nizab zakat assets, 3) How does Islamic law review the public understanding regarding haul and nizab zakat assets in Lagading Village, Pitu Riase District, Sidenreng Rappang Regency. This research is a field research or field research that is descriptive in nature which is expected to provide a comprehensive and systematic picture of facts related to human problems and their symptoms. The results of this study are the people of Lagading Village, Pitu Riase District, Sidrap Regency only know that zakat is an obligation as Muslims, but many do not know the purpose and function of zakat. Most people don't know what nisab and haul are so that in issuing zakat a lot of them are just guessing in accordance with sincerity, while the efforts of the Lagading village government in providing public understanding of haul and nisab zakat assets are to form a village zakat committee which has been running for 10 years. In the past, apart from that, the village head of the Sidrap district has held meetings in the district to conduct training or seminars, and the village government's efforts in fostering the community are to bring in ustadz to discuss zakat at certain times, especially in the month of Ramadan, meanwhile if it is reviewed in law What Islam has prepared and implemented so far is not zakat, but alms, infaq or the like. To make the implementation of zakat efficient in educating Community members need to go through the implementation of programs for this. It is necessary to carry out as soon as possible training or seminars that have been discussed in the district to foster communities related to issuing zakat on assets. It is necessary to immediately formulate the vision, mission and organizational goals of the Amil Zakat Agency in Lagading Village so that the implementation process (both collection and distribution) can be measurable, efficient and on target. It is necessary to collaborate between the government and the community to carry out zakat empowerment movements with various economic development ideas and productive efforts in order to create a prosperous society. Keywords: Islamic Law, Society, Understanding, Zakat